2019
DOI: 10.1002/cbic.201800704
|View full text |Cite
|
Sign up to set email alerts
|

Several Polyphosphate Kinase 2 Enzymes Catalyse the Production of Adenosine 5′‐Polyphosphates

Abstract: Polyphosphate kinases (PPKs) are involved in many metabolic processes; enzymes of the second family (PPK2) are responsible for nucleotide synthesis fuelled by the consumption of inorganic polyphosphate. They catalyse the phosphorylation of nucleotides with various numbers of phosphate residues, such as monophosphates or diphosphates. Hence, these enzymes are promising candidates for cofactor regeneration systems. Besides adenosine 5′‐triphosphate, PPK2s also catalyse the synthesis of highly phosphorylated nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…In a recent study, four PPK2 enzymes derived from classes I, II, and III were shown to produce adenosine 5′‐polyphosphate molecules, such as adenosine tetra‐ (AP4) and pentaphosphate (AP5) by using AMP or ADP and polyphosphate as substrates . We also observed a similar result with DtCs.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…In a recent study, four PPK2 enzymes derived from classes I, II, and III were shown to produce adenosine 5′‐polyphosphate molecules, such as adenosine tetra‐ (AP4) and pentaphosphate (AP5) by using AMP or ADP and polyphosphate as substrates . We also observed a similar result with DtCs.…”
Section: Resultssupporting
confidence: 79%
“…In addition, DtCs showed similar substrate preference to that of another previously characterized enzyme belonging to the same cluster. Our results provide a further understanding of the activity of the PPK2 class III enzymes, and provide clues to the underlying mechanism of the synthesis of adenosine polyphosphate observed in a recent study …”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…PPKs recently reported to be also able to transfer more than one phosphate unit in a single event were not considered for use in this work. [20] In addition to the selection of PPKs, shorter polyphosphate chains are expected to be no efficient donors [15] and therefore, an appropriate excess of polyP mustbep rovided. Figure 2c learly shows that am inimum amount of 40 mm polyP (calculation based on ortho-phosphate units) is required to reach complete reduction of 10 mm of 1a in vitro.…”
mentioning
confidence: 99%